Coordinate modulation of D-glucose transport activity and bilayer fluidity in plasma membranes derived from control and insulin-treated adipocytes. - Pilch, P F (1980)
The cis-monoenoic fatty acids vaccenate and oleate stimulate D-glucose transport when partitioned into isolated plasma membranes from rat adipocytes. The magnitude of hexose transport stimulation due to these agents is equal to that observed in plasma membranes derived from insulin-treated adipocytes. Addition of cis-unsaturated fatty acids to plasma membranes derived from insulin-treated cells results in no further stimulation of glucose transport over that due to the hormone alone. In contrast, treatment of membranes exhibiting insulin-activated D-glucose transport activity with saturated fatty acids reduces transport activity to control levels. No effect of the saturated fatty acids was observed on D-glucose transport in control membranes. Because cis-unsaturated fatty acids fluidize plasma membranes under the conditions used in these experiments, these data demonstrate a positive correlation between membrane fluidity and adipocyte D-glucose transport system activity. In addition, the results suggest that enhanced bilayer fluidity or increased affinity of the glucose transporter for fluid microenvironments of the membrane may play a key role in transport regulation by insulin.